Application of Max-Plus Algebra for Time Optimization of Wooden Furniture Production System “Berkah Usaha” Jepara Regency - Khulda, Ifrikhatul; Isnarto, Isnarto (Pattimura University, 2024)
This research aims to provide a periodic schedule on the Berkah Usaha wood furniture production system in Jepara using Max-Plus Algebra. The data required in the research is data on the flow and processing time of each project work unit. In this research, the main focuses on the Berkah Usaha wooden furniture dining table production system whose processing stages consist of raw material preparation, measurement, wood cutting, wood smoothing, measurement of puruses and holes, table floor manufacturing, puruses and holes manufacturing, table floor smoothing, assembling, sanding, and finishing. The techniques of data collection used in this research are interviews and field observations. Then, a directed graph and model of the Berkah Usaha wood furniture production system were compiled based on the flow data, processing time for each project work unit, and the rules for applying Max-Plus Algebra to the scheduling system. Analysis of the Max-Plus Algebra model of the Berkah Usaha wooden furniture production system using the Power Algorithm with Scilab software assisted. The results of the analysis obtained the production time period of the Berkah Usaha wooden furniture for 253 minutes and the optimal time to start production on each processing unit are 0, 11, 46, 92, 115, 117, 127, 137, 155, 195, 223 time units (in minutes).